KARAKTERISTIK VIRGIN COCONUT OIL (VCO) YANG DI PANEN PADA BERBAGAI KETINGGIAN TEMPAT TUMBUH - Damin, Sardi Hi.; Alam, Nur; Sarro, Dastar (AGROTEKBIS, 2017)
Coconut (Cocos nucifera. L) is a plant that is very useful in the life of the rural economy. Because all parts of the coconut tree could be utilized to meet human needs. One part of the coconut that has many benefits is the coconut meat in the capture milk to be made in pure coconut oil. Aim of this study was to determine the characteristics (yield, degree of clarity and composition of fatty acids) in the VCO coconut harvested at various heights a place to grow. This research was conducted in the territory high level 0-50, 100-150 and 200-250 m above sea level in the district of Parigi Moutong In the Laboratory of Agricultural Technology Faculty of Agriculture, University Tadulako. Implementation of the study began in December 2015 - March 2016. The study design was used way completely randomized design (CRD) with the treatment of the harvested fruit in 3 grades altitude growing ie 1 = 0-50 meters above sea level, 2 = 100-150 meters asl, 3 = 200-250 meters above sea level. Each treatment was repeated five times. The research were showed altitude 0-50 m above sea level provide the highest daily temperatures were significantly different from the temperature elevation 100-150 and 200-250 m above sea level.Key words : Coconut, Virgin Coconut Oil, and Level Growing